Radial distribution of a single-pass amplified radiation in the active elements of CuBr lasers; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Gubarev F. A. Fedor Aleksandrovich (2015, 2015)
Title screen